2018
DOI: 10.5194/gmd-11-1467-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling canopy-induced turbulence in the Earth system: a unified parameterization of turbulent exchange within plant canopies and the roughness sublayer (CLM-ml v0)

Abstract: Abstract. Land surface models used in climate models neglect the roughness sublayer and parameterize within-canopy turbulence in an ad hoc manner. We implemented a roughness sublayer turbulence parameterization in a multilayer canopy model (CLM-ml v0) to test if this theory provides a tractable parameterization extending from the ground through the canopy and the roughness sublayer. We compared the canopy model with the Community Land Model (CLM4.5) at seven forest, two grassland, and three cropland AmeriFlux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(175 citation statements)
references
References 75 publications
2
145
0
Order By: Relevance
“…In general, it appears that CLM u ∗ has a low‐bias relative to the observed u ∗ of around 0.1 m s −1 . Many flux observations sites show a similar u ∗ bias with CLM4.5 (e.g., Bonan et al, ). Because u ∗ is such an important variable, we circumvented this issue by using observed u ∗ as an input to CLM4.5 (see Table for specific configurations).…”
Section: Resultsmentioning
confidence: 68%
“…In general, it appears that CLM u ∗ has a low‐bias relative to the observed u ∗ of around 0.1 m s −1 . Many flux observations sites show a similar u ∗ bias with CLM4.5 (e.g., Bonan et al, ). Because u ∗ is such an important variable, we circumvented this issue by using observed u ∗ as an input to CLM4.5 (see Table for specific configurations).…”
Section: Resultsmentioning
confidence: 68%
“…Improvements to SNOWPACK by Gouttevin et al () and this study focused mainly on the impact of radiation. However, Bonan et al () found turbulence parameterizations having a substantial impact on, among other variables, radiative temperature and reduced overestimation of diurnal ranges by implementing a roughness sublayer and subdividing the vegetation layer.…”
Section: Discussionmentioning
confidence: 99%
“…The multilayer canopy model described by Bonan et al () with the Harman and Finnigan (, ) analytic roughness sublayer mixing scheme shows potential for prognostic simulation of canopy vertical exchange. While the Harman and Finnigan (, ) scheme relies on K‐theory, its introduction of a length scale associated with the turbulent eddies produced by wind shear at the canopy top incorporates the influence of countergradient transport.…”
Section: Theory Models and Observations Of Terrestrial Ozone Deposimentioning
confidence: 99%
“…While the Harman and Finnigan (, ) scheme relies on K‐theory, its introduction of a length scale associated with the turbulent eddies produced by wind shear at the canopy top incorporates the influence of countergradient transport. Bonan et al () find that the Harman and Finnigan (, ) scheme improves simulation of friction velocity and ambient temperature at several forest and grassland sites. With a multilayer canopy large eddy simulation (LES) model explicitly resolving turbulence above and in a forest canopy, Patton et al () show atmospheric stability exerts a control on vertical exchange at the top of the canopy through the structure of the atmospheric boundary layer, suggesting roughness sublayer parameterizations consider the effect.…”
Section: Theory Models and Observations Of Terrestrial Ozone Deposimentioning
confidence: 99%
See 1 more Smart Citation